2020
DOI: 10.1177/0193945920956970
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Moral Distress, and Workplace Engagement in Emergency Department Nurses

Abstract: This cross-sectional, correlational study’s purpose was to evaluate the effects of resilience and moral distress on workplace engagement in emergency department nurses providing direct patient care. Data were collected from 175 emergency department nurses using a Web-based survey. The higher the nurses’ resilience and the lower their moral distress, the greater their workplace engagement. Resilience and moral distress were not correlated; furthermore, moral distress did not mediate a relationship between resil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 39 publications
5
78
0
1
Order By: Relevance
“…M = 108.9, SD = 70.70; Epstein et al, 2019 ), and comparable to moral distress research conducted among non-Canadian HCWs during the COVID-19 pandemic (e.g. M = 113.4, SD = 60.30; Clark, Crawford, Hulse, & Polivka, 2021 ). The most frequently encountered morally distressing events, according to our sample, included witnessing low quality patient care due to poor team communication (82.9%), watching patient care suffer because of a lack of provider continuity (80.2%), and experiencing lack of administrative action or support for a problem that was compromising patient care (78.6%).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…M = 108.9, SD = 70.70; Epstein et al, 2019 ), and comparable to moral distress research conducted among non-Canadian HCWs during the COVID-19 pandemic (e.g. M = 113.4, SD = 60.30; Clark, Crawford, Hulse, & Polivka, 2021 ). The most frequently encountered morally distressing events, according to our sample, included witnessing low quality patient care due to poor team communication (82.9%), watching patient care suffer because of a lack of provider continuity (80.2%), and experiencing lack of administrative action or support for a problem that was compromising patient care (78.6%).…”
Section: Resultssupporting
confidence: 64%
“…The aim of this study was to evaluate the associations between workplace experiences during COVID-19, moral distress, and the psychological well-being of HCWs. Unsurprisingly, moral distress scores were comparable to those found in studies conducted in a USA sample during the COVID-19 pandemic (Clark et al, 2021 ), and were higher than studies conducted prior to the COVID-19 pandemic (Epstein et al, 2019 ). Interestingly, events endorsed in the current study as the most morally distressing included, for example, compromised quality of patient care as evidenced by lack of team support, provider continuity, and overburdened patient loads, as well as experiencing lack of support from administration.…”
Section: Discussionsupporting
confidence: 58%
“…However, this did not reach statistical significance on the convergent validity test. Many studies recently analyzed the correlation between resilience measured using the CD-RISC 2 scale and MD, with diverging results [ 46 , 47 ]. In addition, the latest MD mitigation strategies have development of moral resilience as a goal.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Resilient nurses may experience greater workplace engagement and lower workplace stress, which decreases the likelihood they would leave their jobs. 8 A 2018 online survey 9 of emergency department (ED) nurses found that resilience and job satisfaction predicted workplace engagement, whereas moral distress was negatively related to workplace engagement. Building on this work, we sought to further explore the association of variables and workplace engagement and the nature of workplace engagement in a subsample of participants.…”
Section: Implications For Nursing Managementmentioning
confidence: 99%